The Qualification of Electricity Production in High Efficiency Cogeneration for the Access to the Support Scheme through Green Certificates - Atanasoae P.; Pentiuc R. D. (Problems of the Regional Energetics)
The promotion of high efficiency cogeneration is a priority of the European Union, given the potential benefits of cogeneration relating to primary energy savings, avoiding network losses and reducing emissions of greenhouse gases. The paper presents the manner of determining the amount of electricity generated in high efficiency cogeneration for access to the support scheme through green certificates. The support scheme for the promotion of cogeneration is based on useful heat demand and primary energy savings compared with separate production of electricity and heat. We examine a cogeneration heat and power plant with ORC technology and biomass fuel, which have the technical characteristics in the nominal conditions of 1.3 MWe (electrical power) and 5.4 MWth (thermal power). We also propose an algorithm for determining the useful heat, who takes into account the operational requirements of the analysed CHP unit.